Perkembangan Pemikiran Neo-Lombrosian : Sebuah Tinjauan Teoretis terhadap Determinisme Biologis dalam Kriminologi - Zul Khaidir Kadir (Lembaga Pengembangan Kinerja Dosen, 2025)
In the late 20th and early 21st centuries, despite the decline of classical biological theory, the idea that biological factors play a role in criminal behavior has again gained attention, especially with the emergence of new fields of study such as neurocriminology and behavioral genetics. This approach, often referred to as Neo-Lombrosianism, updates the old biological theory by integrating new findings from modern science. Unfortunately, while the findings of genetics and neurobiology offer a new landscape for searching for the causes of crime, they risk ignoring the important role of social factors such as poverty, opportunity, social processes, trauma, and structural injustice. This study used a data collection method collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study indicate that Neo-Lombrosianism has made a significant contribution to the understanding of the relationship between biological factors and criminal behavior, this approach must be balanced with a full awareness of the importance of social, economic, and environmental factors in influencing human behavior. However, there is a great risk that genetic findings can be used to support unfair policies, especially if biological factors are considered to be the main determinants of criminal behavior.